BIOVIABILITY OF BIDURI LEAF EXTRACT (Calotropis Gigantea L.) ON FIBROBLAST CELL CULTURE - Setyaningsih, Sari; Astuti, Pudji; Meilawaty, Zahara; Dharmayanti, Agustin Wulan Suci (Meditory : The Journal of Medical Laboratory, 2025)
Background: Biduri is recognized for its medicinal properties, particularly in wound healing. The active compounds influence the number of fibroblast cells, which play a role in wound healing. Research on the bioviability of biduri leaf extract has never been conducted, so in vitro testing is necessary to determine the ability of biduri leaf extract to influence fibroblast cells.Objective:  To assess the effect of Biduri leaf extract on the viability of BHK-21 fibroblast cells in vitro. Methods: This experiment used a posttest-only group Design with an MTT assay to assess the viability of BHK-21 fibroblast cells after exposure to different concentrations of Biduri leaf extract. The study employed four treatment groups with varying extract concentrations and used one-way ANOVA followed by an LSD test to analyze the proportion of living cells statistically.Results:  The viability percentages of fibroblast cells varied with the concentration of Biduri leaf extract. The highest viability was observed at 5% concentration (80.82%), while the lowest was at 20% concentration (60.25%). A one-way ANOVA test was used to analyze the data, and differences were considered statistically significant at p 0.05..Conclusions: The highest viability was observed at 5%, while the lowest was at 20% concentration. All treatment groups had cell viability above 60%, indicating that the Biduri extract is generally biocompatible with fibroblast cell culture.